HEALTH EDUCATION TO IMPROVE MEDICATION ADHERENCE AMONG TUBERCULOSIS PATIENTS: A SYSTEMATIC REVIEW - Qomariyah, Farida Nur; Susanti, Ika Adelia; Basri, Achmad Ali (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2024)
Introduction: Adherence to tuberculosis (TB) therapy is critical for the cure. This paper aimed to review current evidence on the effect of health education interventions on medication adherence among patients with tuberculosis.Methods: A systematic review of this study used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Six databases were included in this study including Scopus, Ebsco, PubMed, ProQuest, Science Direct, and Google Scholar published between 2011 and 2020. This study targeted patients with TB, and health education intervention will be extracted. The Joanna Briggs Institute (JBI) Critical Appraisal tools used the level of evidence, grade of recommendation, and risk of bias assessment.Results: Eleven articles were enrolled in the study. Most of all the health education programs have satisfactory results in improving medication adherence among tuberculosis patients. There are many strategies to carry out health education, from conventional ways to the use of technology in order to find the best results to improve compliance. There are seven types of interventions, and the most widely used are individual, paper-based, audiovisual, and education with the reminder. The frequent duration of health education intervention was 1-2 months.Conclusion: An appropriate health education program can improve medication adherence in patients with tuberculosis. This strategies can implement in clinical and community settings to increase health status among tuberculosis patients.